Patients and families as partners in safety, quality, and experiences of care - Amy Jones; Kathy Dutton (The Beryl Institute, 2014)
This case examines the highlights of Vidant Health's journey to a more intentional focus on patient experience. Organizational inconsistencies lead to a focused long term plan putting a culture of patient centeredness at the core of Vidant's efforts. The results show a clear and measured improvement in safety, quality and experience overall.